Preparation of monolithic polycaprolactone foams with controlled morphology. (31st January 2018) - Onder, Ozgun Can; Yilgor, Emel; Yilgor, Iskender
Abstract: Polycaprolactone (PCL) foams were produced by thermally induced phase separation. Tetrahydrofuran/methanol (THF/MeOH) (solvent/non-solvent) mixture was used for the induction of liquid-liquid phase separation of PCL solutions at three different temperatures. Subsequent solvent exchange followed by vacuum drying yielded polymeric foams with different morphologies. Characterization of foams was obtained by scanning electron microscopy, x-ray diffractometry, mercury intrusion porosimetry and compression tests. Influence of polymer concentration (8, 10 and 12 wt%), quench temperature (4,  −20 and −80 °C), and THF/MeOH ratio from (42/58) to (54/46) (wt/wt) on the foam formation, morphology and properties were investigated systematically. Lower PCL concentration, lower THF content and higher quench temperature lead to larger pore sizes in the foams obtained. Detailed discussions of the influence of processing parameters on foam structure and porosity, foam density, percent crystallinity and compressive properties are provided. By selectively tuning the process parameters, foams with controlled pore sizes (10–450 μm), porosity (83–91%) and morphology (cellular, bead-like, microspherical) were obtained. Graphical abstract: Highlights: Microporous PCL foams were prepared by thermally induced phase separation. Tetrahydrofuran/methanol solvent system was used for the induction of liquid-liquid phase separation of PCL. Effect of solvent composition, PCL concentration and quench temperature on foam properties were investigated. Low PCL concentration, low THF content and high quench temperature led to foams with larger pore sizes. Foams were characterized by FTIR, SEM, XRD and porosity measurements.